One-step Procedure for the Preparation of oxazolinyl-zinc Complexes by the Atom-efficient Assembly - Mei Luo; Jing Cheng Zhang; Wen Min Pang; King Kuok Hii (Current Topics on Chemistry and Biochemistry Vol. 3, 2022)
The present study report a simple, one-pot procedure for the preparation of oxazolinyl-zinc complexes by the atom-efficient assembly of three reactive components: a nitrile, an amino alcohol and a zinc salt. Typically, oxazolinyl metal complexes are synthesized in two steps, where the free ligand is prepared by the condensation reaction between a functionalized nitrile and an amino alcohol in the presence of a Lewis or Brønsted acid catalyst, followed by a further reaction with metal salts to obtain the corresponding metal complexes. The yield of the two-step process is frequently low, and just a few oxazolinyl zinc complexes have been synthesised this way. It’s possible that the two stages could be combined because metal-oxazoline complexes frequently comprise Lewis acidic metals. A series of novel chiral organozinc complexes 1–15 were assembled in a single step, All crystalline compounds were fully characterized, including the report of 15 X-ray crystal structures, including a wide structural diversity. A series of novel chiral organozinc complexes were assembled in a single step, from nitriles, chiral D/L amino alcohols, and a stoichiometric amount of ZnCl2, with moderate to high yields (20–90%). The existence of additional donor atoms, reaction stoichiometry, and nature of the -substituent at the stereogenic centre all influence the reaction outcome, resulting in a range of coordination modes, including mono- and bis-chelate complexes. The use of too much zinc salt resulted in multinuclear complexes forming.